2016
DOI: 10.18632/oncotarget.12038
|View full text |Cite
|
Sign up to set email alerts
|

COL3A1 and SNAP91: novel glioblastoma markers with diagnostic and prognostic value

Abstract: Although patients with glioblastoma (GBM) have grave prognosis, significant variability in patient outcome is observed. This study aims to identify novel targets for GBM diagnosis and therapy. Microarray data (GSE4290, GSE7696, and GSE4412) obtained from the Gene Expression Omnibus was used to identify the differentially expressed genes (DEGs) by significant analysis of microarray (SAM). Intersection of the identified DEGs for each profile revealed 46 DEGs in GBM. A subset of common DEGs were validated by real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 44 publications
3
52
0
Order By: Relevance
“…The data showed that an elevated level of H2AFJ transcript predicts a poor overall survival (OS) rate in the unclassified patients or patients with LGG or GBM in a Kaplan-Meier analysis under a maximal risk condition ( Figure 2B). To further confirm the prognostic significance of H2AFJ in GBM, we utilized three Gene Expression Omnibus (GEO) datasets GSE13041 [24], GSE4412 [25], and GSE42669 [26] to perform another Kaplan-Meier analysis of H2AFJ gene expression. The data showed that the elevation of the H2AFJ transcript was significantly (p < 0.01) associated with a poor survival rate in glioma patients in those three datasets ( Figure 2B).…”
Section: H2afj Upregulation Is Highly Correlated With a Poor Prognosimentioning
confidence: 99%
“…The data showed that an elevated level of H2AFJ transcript predicts a poor overall survival (OS) rate in the unclassified patients or patients with LGG or GBM in a Kaplan-Meier analysis under a maximal risk condition ( Figure 2B). To further confirm the prognostic significance of H2AFJ in GBM, we utilized three Gene Expression Omnibus (GEO) datasets GSE13041 [24], GSE4412 [25], and GSE42669 [26] to perform another Kaplan-Meier analysis of H2AFJ gene expression. The data showed that the elevation of the H2AFJ transcript was significantly (p < 0.01) associated with a poor survival rate in glioma patients in those three datasets ( Figure 2B).…”
Section: H2afj Upregulation Is Highly Correlated With a Poor Prognosimentioning
confidence: 99%
“…ncifcrf.gov/) 20 is a publicly available high-throughput functional annotation tool that aim to provide functional interpretation of large lists of genes derived from genomic studies. DAVID database was used to perform GO function and pathway analysis of the common DEGs, 21 using p-Value < 0.05 and count ≥ 2 as cut-off point criteria.…”
Section: Go and Pathway Enrichment Analysis Of Degsmentioning
confidence: 99%
“…Therefore, the study and discovery of glioma biomarkers can provide important references for the accurate diagnosis and treatment of glioma. chemotherapy sensitivity of glioma patients [8][9][10][11]. However, these markers have limited sensitivity and accuracy [12].…”
Section: Introductionmentioning
confidence: 99%